Gender in Civil Engineering Education: A Case Study of the University of Ibadan, Nigeria and Institut d’Enseignement Superieur de Ruhengeri,Rwanda. (2022)
Engineering and technology are basic in any country’s development. Addressing the gender gap in civil engineering education will help to narrow the gender pay gap, enhance women’s economic security and ensure a diverse and talented STEM workforce. This paper focuses on gender disparity in civil engineering education at Institut d’Enseignement Superieur de Ruhengeri (INES), Rwanda, and the University of Ibadan (UI), Nigeria. Data were sourced from the graduating records of the Departments of Civil Engineering, INES Ruhengeri, Rwanda, and the University of Ibadan, Nigeria, covering a period of 5 years (2016 - 2021). Data were analysed using excel tools. The Department of Civil Engineering, University of Ibadan, recorded a slight increase in the number of female graduating students from 5 in the 2015/16 session to 6 in the 2020/21 session, representing a 20% increment and a slight reduction in the number of male graduating students in the department from 37 in the 2016/17 session to 28 in the 2020/21 session representing a 32% reduction. At INES, Ruhengeri, the number of male graduating students in the Department of Civil Engineering increased from 46 in the 2016/17 session to 145 in 2020/21, showing a 215% increment, and the number of female students increased from 18 in 2016/17 to 23 in 2020/21 showing an increment of 28%. The overall percentage of females in civil engineering education is below 20% compared to over 80% of males in the two institutions. Although the number of male graduating students decreases as the year progresses, the increase in female graduating students is not significant. Hence the gender gap seems to remain with year progression. The study proposes an improvement in motivating female students by providing scholarships, including pedagogical motivation in science courses